Heart Failure in Africa, Asia, the Middle East and South America: The INTER-CHF study. (1st February 2016) - Dokainish, Hisham; Teo, Koon; Zhu, Jun; Roy, Ambuj; AlHabib, Khalid F.; ElSayed, Ahmed; Palileo-Villaneuva, Lia; Lopez-Jaramillo, Patricio; Karaye, Kamilu; Yusoff, Khalid; Orlandini, Andres; Sliwa, Karen; et al.
Abstract: Background: There are few data on heart failure (HF) patients from Africa, Asia, the Middle East and South America. Methods: INTER-CHF is a prospective study that enrolled HF patients in 108 centers in 16 countries from 2012 to 2014. Consecutive ambulatory or hospitalized adult patients with HF were enrolled. Baseline data were recorded on sociodemographics, clinical characteristics, HF etiology and treatments. Age- and sex-adjusted results are reported. Results: We recruited 5813 HF patients: mean(SE) age = 59(0.2) years, 39% female, 65% outpatients, 31% from rural areas, 26% with HF with preserved ejection fraction, with 1294 from Africa, 2661 from Asia, 1000 from the Middle-East, and 858 from South America. Participants from Africa—closely followed by Asians—were younger, had lower literacy levels, and were less likely to have health or medication insurance or be on beta-blockers compared with participants from other regions, but were most likely to be in NYHA class IV. Participants from South America were older, had higher insurance and literacy levels, and, along with Middle Eastern participants, were more likely to be on beta-blockers, but had the lowest proportion in NYHA IV. Ischemic heart disease was the most common HF etiology in all regions except Africa where hypertensive heart disease was most common. Conclusions: INTER-CHF describes significant regional variability in socioeconomic and clinical factors, etiologies and treatments in HF patients from Africa, Asia, the Middle East and South America. Opportunities exist for improvement in health/medication insurance rates and proportions of patients on beta blockers, particularly in Africa and Asia.